2021
DOI: 10.1186/s12859-021-04456-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prognostic signature of patients with esophagus adenocarcinoma by using immune-related genes

Abstract: Background Esophageal adenocarcinoma (EAC) is an aggressive malignancy with a poor prognosis. The immune-related genes (IRGs) are crucial to immunocytes tumor infiltration. This study aimed to construct a IRG-related prediction signature in EAC. Methods The related data of EAC patients and IRGs were obtained from the TCGA and ImmPort database, respectively. The cox regression analysis constructed the prediction signature and explored the transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This complex recruits the deubiquitinating enzyme UCH37 to the 26S proteasome 40 . In tumors, the 12 prognosis-related genes including ADRM1 might be promising therapeutic targets esophageal adenocarcinoma 41 . RA190, a specific inhibitor of ADRM1, induces apoptosis intrahepatic cholangiocarcinoma cells 42 .…”
Section: Discussionmentioning
confidence: 99%
“…This complex recruits the deubiquitinating enzyme UCH37 to the 26S proteasome 40 . In tumors, the 12 prognosis-related genes including ADRM1 might be promising therapeutic targets esophageal adenocarcinoma 41 . RA190, a specific inhibitor of ADRM1, induces apoptosis intrahepatic cholangiocarcinoma cells 42 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous similar study also investigated the prognostic factor, immune cell infiltration, and immune-related pathways in EAC [ 82 ]. Zhang et al found 12 IRGs (ADRM1, CXCL1, SEMG1, CCL26, CCL24, AREG, IL23A, UCN2, FGFR4, IL17RB, TNFRSF11A and TNFRSF21) in EAC.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, CCL26, CCL24, AREG, IL23A, TNFRSF11A, and TNFRSF21 were independent risk factors in EAC. Immune cell infiltration analysis showed that M0 was positively correlated with the high-risk group, while M1 and plasma cells were positively correlated with the low-risk group [ 82 ], but they did not explore the immune-related pathways in EAC. In the present study, we constructed an IRGS based on multivariate Cox regression analysis, and we found UNC93B1 and HSPA14 are the independent risk factors in EAC.…”
Section: Discussionmentioning
confidence: 99%
“…TNFRSF21 is the member of the TNF receptor superfamily. Studies suggested that TNFRSF21 might serve as a prognostic marker for esophageal squamous cell carcinoma ( Qiu et al, 2021 ) and esophagus adenocarcinoma ( Zhang et al, 2021 ). Furthermore, it should be mentioned that the impact and mechanism of these seven NRGs in HCC have not been reported yet, and future experiments are needed to provide more evidence.…”
Section: Discussionmentioning
confidence: 99%